Susceptibility analysis on influencing factors of rockfalls and landslides in Tibet - Sen WU; Wen ZHANG; Minsheng LIU (Zhongguo dizhi zaihai yu fangzhi xuebao, 2023)
Geological disasters such as rockfalls and landslides are common in the Tibet region due to its complex topography, strong tectonic movements, and diverse climate conditions. These disasters have an increasingly significant impact on the region's economic construction and social development. In order to assess the susceptibility of rockfalls and landslides in a quantitative manner, this study selected eight factors, including slope, aspect, topographic relief, slope shape, elevation, distance to fault, river density, and engineering geological group, to conduct the sensitivity analysis of the influencing factors by applying GIS and certainty factor analysis methods. The research shows that there is a direct correlation between rockfall, landslide and influencing factors, and the susceptibility of these hazards is high in the areas with: (1) a slope greater than 30°, (2) aspect facing southeast, south, or southwest direction, (3) topographic relief of 200～800 m/km2, (4) concave slope, (5) elevation between 1500 and 4500 m, (6) distance between 0 and 3 km to fault, (7) river density greater than 0.5 km/km2, (8) lithologies identified by the codes of YJ2, TS1, TS2, and BZ1. The susceptibility of the factors is ranked in descending order as slope > engineering geological group > elevation > slope shape > river density > topographic relief > aspect > distance to fault. These results can be used as a reference for assessing the susceptibility of rockfalls and landslides in Tibet.